Elucidation of synergism in Ce-Zr/SBA-15 mesoporous catalysts and the effects on the activity in selective glycerol to lactic acid reaction - Syamima Nasrin, Mohamed Saleh; Muhammad Yusri, Ahmad; Anwar, Ul-Hamid; Ahmad Zuhairi, Abdullah (Elsevier B.V., 2024)
The continued conversion of glycerol to value-added chemicals is essential in ensuring the sustainable development of the biodiesel industry. Selective catalytic oxidation of glycerol to lactic acid provides an alternative approach to valorizing glycerol. A mesoporous SBA-15 supported mixed-metallic oxide catalyst is deemed essential to selectively produce lactic acid in this mixed parallel and multi-step reaction. SBA-15-supported bimetallic Ce and Zr oxides were proved to be highly efficient catalysts for the selective glycerol oxidation into lactic acid in base-free media. The synergism between Ce and Zr in the bimetallic oxide compounds could enhance the creation of oxygen vacancies in the catalyst via the reduction of Ce4+ to Ce3+. The 2:1CeZr/SBA-15 catalyst exhibited prominent catalytic activity in selectively oxidizing glycerol to lactic acid, with a glycerol conversion of 91.8 and a lactic acid yield of 35.1. This work achieved superior catalytic performance compared to previously conducted studies, primarily due to the significantly higher initial glycerol concentration employed in this study. To ascertain the intrinsic active sites of the catalyst, the physicochemical properties of the catalyst were thoroughly examined using BET, FTIR, XRD, FESEM, TEM, CO2-TPD, O2-TPD, and H2-TPR analysis. This work concluded that the synergistic interaction of the active sites, which led to the formation of active oxygen species, facilitated primary dehydrogenation of the terminal -OH bond in glycerol. Hence, in this work, a plausible glycerol conversion mechanism over the 2:1CeZr/SBA-15 catalyst was also proposed.